2018
DOI: 10.3390/electronics7090181
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Based Quartz Crystal Microbalance for Alcohol Sensing

Abstract: Short-chain alcohols are a group of volatile organic compounds (VOCs) that are often found in workplaces and laboratories, as well as medical, pharmaceutical, and food industries. Real-time monitoring of alcohol vapors is essential because exposure to alcohol vapors with concentrations of 0.15–0.30 mg·L−1 may be harmful to human health. This study aims to improve the detection capabilities of quartz crystal microbalance (QCM)-based sensors for the analysis of alcohol vapors. The active layer of chitosan was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 26 publications
1
26
1
Order By: Relevance
“…Other works also noted that the sensitivity of the QCM humidity sensor was proportional to the loading mass of its active layer (Wang et al, 2010). However, this result is different from ours, as the highest sensitivity was exhibited by the QCM NF 2, which has medium loading mass.…”
Section: Humidity Sensing Profilecontrasting
confidence: 81%
“…Other works also noted that the sensitivity of the QCM humidity sensor was proportional to the loading mass of its active layer (Wang et al, 2010). However, this result is different from ours, as the highest sensitivity was exhibited by the QCM NF 2, which has medium loading mass.…”
Section: Humidity Sensing Profilecontrasting
confidence: 81%
“…The film mass deposited on the QCM surface was calculated using the Sauerbrey equation [14] and was found to be 20.4 µ g. Figure 4a shows the frequency shift of the QCM exposed to the BTX vapors at a concentration of 622 ppm. Soon after analyte injection into the chamber, the QCM resonant frequency decreased For investigation of the sensing performance of the proposed system, we used the static batch system as reported in the previous works [20,21]. The concentration of the injected analyte in the chamber is expressed in ppm and calculated using the equation available in the previous works [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…The chemical structures of the compounds used in this study are shown in Figure 1. For investigation of the sensing performance of the proposed system, we used the static batch system as reported in the previous works [20,21]. The concentration of the injected analyte in the chamber is expressed in ppm and calculated using the equation available in the previous works [22,23].…”
Section: Methodsmentioning
confidence: 99%
“…The schematic diagram for safrole vapor analysis by the batch system is available in our previous work (Rianjanu et al 2018a;Triyana et al 2018). The QCM sensor was installed in the testing chamber with a volume of 1.25 L.…”
Section: Safrole Sensor Configuration and Experimental Setupmentioning
confidence: 99%
“…Chitosan (Cs) is a natural polymer which consists of a polysaccharide containing the functional groups −OH and −NH 2 and possesses many promising properties such as excellent filmforming ability, high mechanical strength, biodegradability, biocompatibility and antibacterial properties (Ayad et al 2014). Considerable efforts have been devoted to devising gas/vapor sensors using chitosan and its composites as active layers (Ayad & Minisy 2016;Triyana et al 2018;Zhang et al 2017). However, to the best of our knowledge, there has been no effort to develop a promising strategy to modify PAN nanofibers with chitosan and combine these with QCM to construct sensitive safrole sensors.…”
Section: Introductionmentioning
confidence: 99%